NO-independent regulatory site of direct sGC stimulators like YC-1 and BAY 41-2272 - Becker, Eva Maria (BioMed Central, 2001)
BACKGROUND: The most important receptor for nitic oxide is the soluble guanylate cyclase (sGC), a heme containing heterodimer. Recently, a pyrazolopyridine derivative BAY 41-2272, structurally related to YC-1, was identified stimulating soluble guanylate cyclase in an NO-independent manner, which results in vasodilatation and antiplatelet activity. The study described here addresses the identification of the NO-independent site on soluble guanylate cyclase. RESULTS: We developed a photoaffinity label ((3)H-meta-PAL) for the direct and NO-independent soluble guanylate cyclase (sGC) stimulator BAY 41-2272 by introducing an azido-group into the tritium labeled compound. The synthesized photoaffinitylabel directly stimulates the purified sGC and shows in combination with NO a synergistic effect on sGC activity. Irradiation with UV light of (3)H-meta-PAL together with the highly purified sGC leads to a covalent binding to the α(1)-subunit of the enzyme. This binding is blocked by unlabeled meta-PAL, YC-1 and BAY 41-2272. For further identification of the NO-independent regulatory site the (3)H-meta-PAL labeled sGC was fragmented by CNBr digest. The (3)H-meta-PAL binds to a CNBr fragment, consisting of the amino acids 236–290 of the α(1)-subunit. Determination of radioactivity of the single PTH-cycles from the sequencing of this CNBr fragment detected the cysteines 238 and 243 as binding residues of the (3)H-meta-PAL. CONCLUSIONS: Our data demonstrate that the region surrounding the cysteines 238 and 243 in the α(1)-subunit of the sGC could play an important role in regulation of sGC activity and could be the target of this new type of sGC stimulators.